Planning and Elaboration - Royce M. Earnest (Oz, 1989)
Buildings, like people, need to be a part of something larger than themselves, and to be approachable and understandable. Cities which are organized on the scale of society, and whose creation requires scales of time, effort, and resources far beyond any single project, represent this larger view, while the way individuals relate and fit into them determines whether they are humane and pleasant places...